3. Objective (Journal of Parents and Teachers, 2026)
It explains what a learning objective is in education, emphasises the importance of expressing each objective precisely, relating them to concepts, procedures and attitudes, and serves as a guide for teaching and assessing students.
Keywords: Learning objectives, assessment, attitudes and teaching.